The Oxford companion to politics of the world (Oxford, New York, 1993)
The book discusses virtually every nation in the world, and includes extensive information on institutions, political parties, leaders, and the sources of political mobilization and conflict. The book also includes biographies of more than seventy-five political leaders and thinkers who have shaped the contemporary political world, nd detaled discussions of critical historical developments and events, concepts, international law, and organizations
Keywords: political science - encyclopedias,world politics - encyclopedias